Redesigned Straits Times : a better paper? A content analysis on the readability of the Straits Times before and after the revamp - Alsagoff Sharifah Fathiah Anwar (2008)
The straits Times underwent a major revamp in its look on 23 March 1998. The main aim was to make the newspaper more readable so as to capture the youth market and stay in top of the competition from other media.